Prevalence of malocclusion among school Children of Kathmandu, Nepal - Bajracharya, Manju; Sundas, Sunanda; Pradhan, Resina; Maharjan, Surendra (Orthodontic Journal of Nepal, 2019)
Introduction: this study was carried to understand Prevalence of malocclusion among the school children of Kathmandu, Sorakhutte residing near school during mixed dentition period. A sample of 600 children ; 365 male, 235 female in age group of 6-13yrs was selected randomly from different school of Kathmandu city. The aim of our study is to find out prevalence of malocclusion among the mixed detention children of Kathmandu. Materials & Method: Data was collected using direct observation of the subjects, Descriptive cross-sectional study method was used in this research. Occlusal assessment were done according to angle’s classification and dewey’s modification type of class I, class III malocclusion. Result: Subjects with normal occlusion was found to be 59.3% and with malocclusion was found to 40.7%. Among them class I malocclusion was majority of (57%) of study population, crowded incisors and significant difference was observed between male and female in the study. Conclusion: This study helps to access the prevalence malocclusion and need of orthodontic treatment for the mixed dentition period children.